Iowa Birdline update, September 28, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for September 28, 1989. Highlights include Water Pipits, a Merlin, and several Sparrow species. Epson - sheet feed/flatbed